Alcohol misuse—a national pandemic: an investigation to identify whether implementing an alcohol brief intervention service would benefit patients attending an oral and maxillofacial (OMFS) department. (April 2017) - Wright, A.L.; Clark, A.S.E.; Ward, G.; Moodie, F.; Taylor, G.D.; Boyd, D.; Currie, W.J.R.; Hislop, W.S.; Halsnad, S.M.
Highlights: Ayrshire and Arran has significant alcohol intake resulting in a large number of alcohol-related hospital admissions. Oral and Maxillofacial surgery sees many patients for whom their presentation relates to alcohol, in particular oral cancer and trauma. Acute admission and outpatient appointments provide an opportunity to screen and refer patients to alcohol services as required. Presentation to Oral and Maxillofacial department may provide an ideal opportunity for intervention of alcohol use with high-risk patients.